Simplified MD-LSD demapping algorithm for BICM-ID systems with multi-dimensional mappings - GONG Feng-kui; GE Jian-hua; WANG Yong (Tongxin xuebao)
The soft in soft out MAX-LOG-MAP algorithm of conventional mappings was expanded to the BICM-ID sys- tem with multi-dimensional mappings. A multi-dimensional list sphere decoding （MD-LSD） algorithm was also proposed by using the list sphere decoding algorithm of multi-antenna systems. Compared with the MD-MAX-LOG-MAP algo- rithm, the computational complexity of MD-LSD was decreased significantly. Simulation results show that the perform- ance degradation of the simplified MD-LSD algorithm can be ignored when the list length is in a certain range.